Technology Adoption and Business Performance: Evidence from Halal MSMEs in Indonesia - Tikawati Tikawati; Norvadewi Norvadewi; Fitria Rahmah; Arista Wibowo; Selamah Maamor; Shahid Manalundong (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
Digital transformation is essential for improving the competitiveness of halal MSMEs. This study aims to examine the effect of technology adoption (TA) and halal certification on business performance (BP) and to test whether halal certification moderates the relationship between TA and BP among halal micro, small, and medium enterprises (MSMEs) in Indonesia. This quantitative survey study employed purposive sampling and collected data from 110 halal MSMEs through a structured questionnaire. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The results show that TA has a positive and significant effect on BP (b = 0.710, t = 13.168, p 0.001), halal certification also has a positive and significant effect on BP (b = 0.196, t = 2.458, p = 0.014), the model explains 65.3% of the variance in BP (R² = 0.653), and the moderating effect of halal certification is not significant (b = 0.029, t = 0.886, p = 0.376). The results indicate that halal certification and TA are crucial for improving BP. These findings imply that digital TA is the main driver of halal MSME performance, while halal certification functions as a complementary source of legitimacy and consumer trust.